Antibacterial activity of marine macro algae against human pathogens - D. Stella, K. Kolanjinathan (Recent Research in Science and Technology, 2009)
Methanol, ethanol and acetone extracts of six seaweed species from the south east coast of India were tested invitro for their antibacterial activities against bacteria. Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumonia, Enterococcus faecalis with the disc diffusion method. Acetone was the best solution for extracting the antimicrobial materials from the algal species used in this experiment, with the exception of Ulva lactua for which ethanol was the most effective extraction solution. A Significant in antibacterial activity was not observed between the ethanol and methanol extracts of each algae. In addition as a result of the comparison of dried and fresh extract of antibacterial activity, it was found that, all the test organisms were more sensitive to fresh extracts of the algae.